The United Nations General Assembly’s role in the formulation of international custom - Mahmoudi, Hazhar; Seyyed Baqer Mirabbasi, Abu Mohammad Asgarkhani, (Opción, 2019)
The General Assembly within the framework of its charter and authority has enabled the establishment of customary rules that in this research will provide an analytical examination in a library method in the existing judicial and practical procedure in this regard. As a result, if a resolution is merely interpreting the rules of international law, it can be very useful in understanding and applying these rules. In conclusion, the General Assembly of the United Nations has able to create the international custom with its advisory recommendations and issuing resolution and its practical procedure.